Automated home cage monitoring of an aging colony of mice—Implications for welfare monitoring and experimentation - Moore, Joanna L.; Kennedy, James; Hassan, Abdul-Azim (Frontiers in Neuroscience, 2024)
IntroductionOur understanding of laboratory animal behavior and the implications of husbandry activities on their wellbeing remains incomplete. This is especially relevant with an aging colony as their activity patterns may change as they mature. Home Cage Monitoring (HCM) provides valuable insights into mouse activity within the animal's own environment and can shed light on acclimatization periods and responses to husbandry activities such as cage changing. The aim of this study was to monitor and explore changes in the activity and rest disturbance (RDI) patterns of an aging colony of male and female C57/BL6 mice.MethodsThe mice were housed in the Digitally Ventilated Cage® system, for up to 18 months of age. Data was then downloaded to investigate how the activity patterns and RDI of the mice changed over time. Habituation, aging and cage change assessments were conducted using linear mixed models, while cage separation and stereotypic behavior investigations were conducted by visual inspection of the data.ResultsAs expected during the study, mice were less active during the light phase compared to the dark phase. However, on arrival mice displayed heightened activity and RDI during the light phase and reduced activity and RDI during the dark phase, taking several days to adjust to baseline “acclimatized” patterns. With age, overall activity significantly decreased from 5 months until 14 months of age, after which it increased back toward baseline levels. We also observed activity spikes during our monitoring of this colony. Prolonged housing can lead to alarming stereotypic behaviors in animals. Cages of mice flagged for potential stereotypy displayed sustained activity spikes in the light and dark phases. Spikes in activity during the dark phase were much more pronounced than in the light phase. Cage changing led to an increase in the light phase activity and RDI compared to the previous day, with no observed difference in the dark phase post-cage change. This effect remained consistent as the animals aged.DiscussionThis study explores changes in the activity patterns of an aging colony of male and female C57/BL6 mice housed in the Digitally Ventilated Cage® system. We identified distinct aging phases concerning activity and RDI differences and a potential new welfare application for the DVC®, specifically for early detection of stereotypy. In conclusion, the adoption of HCM systems should be considered for long-term animal housing from both a welfare and behavioral perspective.